A systematic literature review to examine the potential for social media to impact HPV vaccine uptake and awareness, knowledge, and attitudes about HPV and HPV vaccination. Issue 7 (3rd August 2019) - Ortiz, Rebecca R.; Smith, Andrea; Coyne-Beasley, Tamera
ABSTRACT: This article summarizes the findings from a systematic literature review to examine how social media may impact HPV vaccine uptake and HPV and HPV vaccine related awareness, knowledge, and attitudes. Study inclusion criteria was original data collection of at least one data point about social media and HPV and/or HPV vaccination, such that the study provided insight into how social media content may influence HPV and HPV vaccine related knowledge, attitudes, and/or behaviors. A total of 44 relevant articles were identified using the following databases: PubMed, PsycINFO, Communication Source, Sociological Abstracts, Business Source Elite, and the Educational Resources Information Center (ERIC). Most studies analyzed the valence, type, and frequency of social media content about HPV vaccination, and some found associations between potential exposure to negative, anti-vacc`11qine content and lower vaccination rates. Some studies that included primary human subject data collection found that engagement with HPV related social media content was associated with improved awareness and knowledge but not with increased vaccine uptake. The literature overall is lacking in systematic and rigorous research examining the effects of social media on HPV related knowledge, attitudes, and behaviors and needs further examination as social media increasingly becomes a source of health information.